Anya’s Posttraumatic Growth Over Her Loss Trauma as Reflected in Natassa’s Critical Eleven - Wijaya, Clara Andita Dwi Putri (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
It has been commonly assumed that trauma only lead to a negative impact on its survivors. However, on another hand, trauma can bring positive changes. This situation is commonly said as post-traumatic growth (PTG). The PTG process takes a quite long time and each survivor has different capabilities and processes to achieve it. Anya, the main character in the novel of Critical Eleven, experiences the trauma of loss after her first baby dies. Since her baby left, Anya has been in a dark period. This research aims to determine the type of loss trauma experienced by Anya. As a trauma survivor, Anya's post-traumatic growth was also explained in this research. Two theories were utilized in this research. Freud's theory of mourning and melancholia was used to analyze the type of loss trauma that Anya experienced. Meanwhile, the post-traumatic growth theory (PTG) proposed by Tedeschi and Calhoun was used to determine Anya's post-traumatic growth domain. The primary data for this research were taken from the novel of Critical Eleven written by Ika Natassa. In addition, research related to traumatic loss and post-traumatic growth was used as supporting data. The research results show that the trauma of loss experienced by Anya is grief or mourning. Furthermore, the PTG domains found in Anya's personality reflected personal strength, inter-personal relationships, and spiritual change. In addition, this research also found that not all trauma survivors can achieve the five domains of post-traumatic growth due to the respective capabilities and life processes of each survivor.